Bagaimana Green Accounting Mempengaruhi Financial Performance Melalui Enviromental Performance Ratings? Studi Empiris: Perusahaan Energi di Indonesia - Hasibuan, Nur Fadhilah Ahmad; Hasibuan, Rahmat Putra Ahmad (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sumatera Utara, 2025)
Green Accounting is very important to be implemented by the energy and mining industry to minimize the environmental impact caused by the Company's production activities. The exploration activities of natural resource production by mining and energy companies result in high air pollution impacts in Indonesia. This study aims to determine the direct and indirect effects of green accounting on financial performance through environmental performance ratings as an intervening variable in LQ45 Energy and Mining Companies listed on the Indonesia Stock Exchange (IDX) for the 2020-2024 period. This study uses quantitative data and secondary data sources from annual reports and sustainability reports. This study uses the method of sampling the entire population (census sampling) with 40 data samples that match the criteria from 8 companies. This study uses a multiple regression model with path analysis. Based on the results of the study, it was found that green accounting directly affects financial performance and enviromental perfomance ratings, but indirectly green accounting does not have a significant effect on financial performance through environmental performance ratings.